Natural resource and sustainability monitoring: a conceptual framework, issues and challenges - Babu, Suresh Chandra (International Food Policy Research Institute, 1997)
Periodic monitoring of the status of natural resources is fundamental to generate adequate information for planning and policymaking towards their sustainable management. This paper provides an overview of the concepts, issues, and challenges that planners and policymakers face in designing natural resource and sustainability monitoring systems and using their outcome in the formulation of policies and intervention programs.